A Novel Approach to Assessing Light Extinction with Decade-Long Observations of Chemical and Optical Properties in Seoul, South Korea - Seung-Myung Park; Jong Sung Park; In-Ho Song; Jeonghwan Kim; Hyun Woong Kim; Jaeyun Lee; Jung Min Park; Jeong-ho Kim; Yongjoo Choi; Hye Jung Shin; Joon Young Ahn; Yu Woon Jang; et al. (Atmosphere, 2024)
We performed continuous long-term measurements of PM2.5 mass, comprehensive chemical composition, and optical properties, including scattering and absorption coefficients, from March 2011 to December 2020 at the Metropolitan Air Quality Research Center in Seoul, South Korea. PM2.5 peaked at 38 μg/m3 in 2013 and has been declining steadily since then, reaching 22 μg/m3 in 2020. The extinction coefficients also decreased with the decline in PM2.5, but the correlation between the two factors was not as pronounced. This deviation was mainly attributed to the rapid changes in the chemical composition of PM2.5 over the same period. The mass contribution of sulphate to PM2.5 decreased from 33.9 to 24.1%, but the fraction of nitrate and organic carbon increased from 23.4 and 20.0 to 34.1 and 32.2%, respectively, indicating that sulphate has been replaced by nitrate and organic carbon over the past decade. To assess the effect of changing aerosol chemical compositions on light extinction, we compared the measured extinction coefficients with those estimated via the various existing light extinction approaches, including the revised IMPROVE algorithm. We found that the simplified linear regression model provided the best fit to our data, with a slope of 1.03 and R2 of 0.87, and that all non-linear methods, such as the IMPROVE algorithms, overestimated the observed long-term light extinction by 23 to 48%. This suggests that the simple linear regression scheme may be more appropriate for reflecting the varying aerosol conditions over long periods of time, especially for urban air. However, for conditions where the chemical composition does not change much, non-linear methods such as the IMPROVE scheme are likely to be more appropriate for reproducing light extinction.